The Unidroit Principles of Contract Law; Is There Room for Their Inclusion into Domestic Contracts? - Zeller, Bruno (Journal of Law and Commerce, 2008)
When the UNIDROIT Principles (the Principles) were published in 1994 they were considered to be “soft law” and hence not binding on the courts. However, these principles have demonstrated that they are offering concrete and worthwhile solutions and arguably are a move forward in harmonizing and unifying contract laws. Indeed, the intention of the UNIDROIT Working Groups was to “develop a set of norms best suited to accommodate the needs of the international commercial community.” The Principles themselves argue that it reflects “concepts to be found in many, if not all, legal systems.” As a result the Principles are not: “a rigid and limitative legal source but instead leave considerable room for flexibility, either to accommodate specific provisions to further individual parties’ interest in their private dealings, or to promote national trade and economic policies. This makes the Principles a unique tool to be adapted into any contract and arguably protect the parties’ just expectations arising from their contract.